Clinical and prognosis value of the number of metastatic lymph nodes in patients with papillary thyroid carcinoma - Ling Zhan; Hong-fang Feng; Xi-zi Yu; Ling-rui Li; Jun-long Song; Yi Tu; Jing-ping Yuan; Chuang Chen; Sheng-rong Sun (BMC Surgery, 2022)
Abstract Objective It has been reported that papillary thyroid carcinoma (PTC) patients with lymph node metastasis (LNM) are largely associated with adverse outcomes. The present study aimed to assess the correlation between the number of metastatic lymph nodes (NMLNs) and clinical prognosis in patients with PTC. Methods We retrospectively reviewed the medical records of patients with PTC who underwent initial thyroid cancer surgery in Renmin Hospital of Wuhan University between 2017 and 2019. A total of 694 patients with PTC and cervical lymph node dissection as well as a total checked number of lymph nodes ≥ 5 were involved in this study. The clinicopathological characteristics of patients were compared according to NMLNs, the number of central cervical lymph nodes (CLNs) and the number of lateral lymph nodes (LLNs). Results NMLNs > 5, CLNs > 5 and LLNs > 5 were 222 (32.0%), 159 (24.3%) and 70 (10.1%) seen in the analyzed samples, respectively. Young patients, patients with larger tumor diameter, bilaterality, multifocality and gross extrathyroidal extension (ETE) were more inclined to NMLNs > 5, CLNs > 5 and LLNs > 5 (P < 0.05). It was found that the recurrence-free survival among pN1 patients was significantly discrepant between different groups (NMLNs ≤ 5/5: P = 0.001; LLNs ≤ 5/5: P < 0.001). In multivariate logistic regression analysis, patients aged < 55 years (OR = 1.917), primary tumor size > 10 mm (OR = 2.131), bilaterality (OR = 1.889) and tumor gross ETE (OR = 2.759) were independent predictors for high prevalence of total NMLNs > 5 (P < 0.05). Specially, patients aged < 55 years (OR = 2.864), primary tumor size > 10 mm (OR = 2.006), and tumor gross ETE (OR = 2.520) were independent predictors for high prevalence of CLNs > 5 (P < 0.01); Bilaterality (OR = 2.119), CLNs > 5 (OR = 6.733) and tumor gross ETE (OR = 4.737) were independent predictors for high prevalence of LLNs > 5 (P < 0.05). Conclusions In conclusion, it is evident that NMLNs is related to the invasive clinicopathological features and adverse outcome of patients with PTC which should be correctly evaluated to provide an appropriate guidance for reasonable treatment and careful follow-up.